Mapping civil society in contemporary Greece: Problems and perspectives - Αφουξενίδης Αλέξανδρος; Γαρδίκη Μαρία (The Greek Review of Social Research, 2015)
The paper presents some of the evidence of a longitudinal study of civil society in contemporary Greece. The various types of organizations are presented according to their corresponding thematic area, while NGOs are looked upon separately. Taking into consideration that the concept of ‘civil society’, or, as it is sometimes called, ‘the third sector’, is a highly contested one, this paper aims at empirically coding and systematizing the sector, leaving the possibilities open for further research and study.